Comment on “Clinical Outcomes of Implantable Collamer Lenses for the Treatment of Myopia in Eyes with Anterior Chamber Depth (<3.0 mm) at a Single Center in the United States” [Response to Letter] - Hirabayashi M; Virdi G; Abramson AJ; Nasser T; Vanrachack A; Parkhurst G (Clinical Ophthalmology)
Matthew Hirabayashi,1 Gurpal Virdi,2,3 Andrew J Abramson,4 Taj Nasser,5 Anthony Vanrachack,1 Gregory Parkhurst1 1Parkhurst NuVision LASIK Eye Surgery, San Antonio, TX, USA; 2University of Missouri Columbia School of Medicine, Columbia, MO, USA; 3Mason Eye Institute, University of Missouri, Columbia, MO, USA; 4Texas State University, San Marcos, TX, USA; 5Tylock George Eye Care and Laser, Irvine, TX, USACorrespondence: Matthew Hirabayashi, Parkhurst NuVision LASIK Eye Surgery, 9725 Datapoint Dr Suite 106, San Antonio, TX, 78229, USA, Tel +1 314 578 2374, Email matthewhirabayashi@gmail.com